Peran Strategis LPBI NU Jombang dalam Isu Lingkungan Global - Iskandar, Winda Nurlaily Rafikalia; Rodhotul Uswatun Chasanah; Latifatul Ilmia; Farah Salsabila (Andalas Institute of International Studies, 2025)
This research focuses on global environmental issues that impact the local level, both in urban and rural areas. Various elements of society are expected to play an active role in responding to global environmental issues, one of which is driven by a religious based organization, Lembaga Penanggulangan Bencana dan Perubahan Iklim Nahdlatul Ulama (LPBI NU) Jombang. The purpose of this research is to examine the role of LPBI NU Jombang in responding to global environmental issues. This research uses the transnational environmental concept by Reiner Grundmann, which links global environmental issues not only the responsibility of government actors but also emphasizes the framework of cooperation between various elements and transnational actors, both governmental and non-governmental actors. This research used qualitative methods and descriptive analysis. Data collection techniques in this research used literature studies and in-depth interview with the head of LPBI NU Jombang. The results of this study indicate that LPBI NU Jombang plays an active role as an agent of change to environmental issues in Jombang. Some programs initiated by LPBI NU Jombang include GASPOL, JAMSENA, and Madrasah Tangguh Bencana. The activities are a collaboration between multi-actors with adapting local conditions. Although the issues and guidelines used by LPBI NU Jombang are international, the resulting solutions prioritize local values to ensure targeted effectiveness.